Saturday

April 19, 2014

April 19, 2014

Posted by **cecile** on Friday, January 4, 2008 at 5:58am.

- maths -
**Damon**, Friday, January 4, 2008 at 7:24amAn = 3 n (2- n^2) / [ 2 n^2 (n+2) ]

An = (3/2) (1/n) (-1) (n^2-2) /(n+2)

as n gets big, 2 looks small

An = (-3/2) (1/n) (n^2/n)

An = -3/2 (n^2/n^2)

An = -3/2

**Related Questions**

geometry - I'm having a hard time with this question: "AB has endpoints A(n,4n) ...

Algebra - Add The following (8n^6 - 6n - 5n^4) + (2n^4 + 2n^6 + 3n) I think that...

math - If n is an integer, which of the following must be odd? a. 3n-5 b. 3n+4 c...

algebra - So... I know the answer to the question because it's something we ...

Maths-Vectors Assistance PLZZ! - Prove that the vectors u=3i+j-2k , v= -i+3j=4k...

Calculus - integral -oo, oo [(2x)/(x^2+1)^2] dx (a) state why the integral is ...

Calculus: Limits - ++++++++|||||||||Can you please check whether or not my ...

Algebra - Add. (8n6 - 6n - 5n4) + (2n4 + 2n6 + 3n) I think I have this answer ...

Calculus II - Determine whether the sequence converges or diverges. If it ...

Calculus - Determine whether the sequence A(n)=nsinn/n^3 converges or diverges. ...